2020
DOI: 10.1111/acel.13166
|View full text |Cite
|
Sign up to set email alerts
|

Age‐induced mitochondrial DNA point mutations are inadequate to alter metabolic homeostasis in response to nutrient challenge

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…Interestingly, there were gender‐specific differences for heart and liver tissues for one variant and generational differences for several tissues for the same variant (G. Cagnone et al, 2016 ). Indeed, the consensus opinion is that mtDNA point mutations associated with mammalian aging are insufficient to cause a phenotypic response (Moore et al, 2020 ). For example, in hair, the exponential increase in mutation with age ranges from 0 to 1.436 ± 0.2086% of total mtDNA content (Zheng et al, 2012 ), which, in the context of mtDNA copy number per cell suggests little if no impact on health and well‐being.…”
Section: The Mitochondrial Genetic Bottleneckmentioning
confidence: 99%
“…Interestingly, there were gender‐specific differences for heart and liver tissues for one variant and generational differences for several tissues for the same variant (G. Cagnone et al, 2016 ). Indeed, the consensus opinion is that mtDNA point mutations associated with mammalian aging are insufficient to cause a phenotypic response (Moore et al, 2020 ). For example, in hair, the exponential increase in mutation with age ranges from 0 to 1.436 ± 0.2086% of total mtDNA content (Zheng et al, 2012 ), which, in the context of mtDNA copy number per cell suggests little if no impact on health and well‐being.…”
Section: The Mitochondrial Genetic Bottleneckmentioning
confidence: 99%
“…They found heterozygous mice had some difference at the molecular level compared with WT mice, but there was no difference in phenotype or life span between heterozygous and WT mice. However, homozygous mice all showed significant pathology damage in mitochondria dysfunction and phenotypes [13,34]. For example, D257A mutant of PolG directed reduced the content of electron transport chain (ETC) complexes I, III and IV which could promote skeletal muscle apoptosis and sarcopenia [35], and Tadafumi et.al constructed same model in PolG +/D257A mice which were recognized had no difference in phenotypes of WT mice [36,37], while they found the motor dysfunction caused by heterozygous mutation PolG was significant milder than that in homozygous mutation mice [38].…”
Section: Discussionmentioning
confidence: 97%
“…PolG D257A mutation mice was constructed as a mitochondria damaged model which the point mutation located in the proof-reading-deficient version of PolG and damaged 3'-5' exonuclease activity of polymerase, resulting in 3-fold to 5-fold increment of mutant mtDNA and increased amounts of deleted mtDNA [1]. Some research also revealed PolG deficiency brought alteration to cellular Ivyspring International Publisher metabolism [12,13]. Thus, PolG was recognized as a crucial stabilization factor of mitochondria, and any deficiency of PolG could damage mitochondrial function and eventually lead to cellular senescence induced by mitochondria.…”
Section: Introductionmentioning
confidence: 99%
“…Reducing Insulin growth factor 1 (IGF1)-mediated signaling is directly related to aging and CVD [7]. Importantly, in the heart IGF1 signaling regulates various cellular mechanisms, including growth, metabolic homeostasis [8], and autophagy [9]. For instance, IGF1 ligand and its receptor, IGF1R interaction starts downstream signaling cascades in cardiomyocytes that eventually regulate their differentiation, proliferation, metabolism, hypertrophy [10], and protection from cell death.…”
Section: Introductionmentioning
confidence: 99%